COLLECTIVE SELF-ESTEEM AND CULTURAL ORIENTATION - Novita W. Sutantoputri; Evanytha Evanytha (MANASA, 2013)
The present study explored the relationship between collective self-esteem and cultural orientation. It was hypothesized that one’s collective self-esteem or one’s judgment of being a member of one’s ethnic group would predict their cultural orientation. Collective self-esteem or one’s judgment of one being a member of one’s ethnic group had 4 dimensions: private, public, membership and importance; cultural orientation also had 4 dimensions: horizontal individualism, horizontal collectivism, vertical individualism, and vertical collectivism. One-hundred and fifty-nine students participated in the present study. Public collective self-esteem positively predicted horizontal individualism (β = .217) and vertical individualism (β = .224); private collective self-esteem positively predicted vertical collectivism, (β = .273) and negatively predicted vertical individualism (β = -.234). Cultural factors, particular to the Indonesian context, need to be taken into account in regard to interpreting the collected data.